Pengaruh Content Marketing dan Live Shopping Terhadap Minat Beli Produk Aerostreet pada Pengguna Tiktok Shop - Alvin Danu Arta, Muhammad; Arqy Ahmadi, Mirzam (Teewan Journal Solutions, 2025)
Social media has now developed very rapidly and plays an important role in marketing, especially on the TikTok platform which provides various features to market products through content and live streaming. This study was conducted to examine how much influence content marketing and live shopping have in increasing interest in buying Aerostreet products among TikTok Shop users. This study uses a quantitative approach, where the population consists of TikTok Shop users who know or have purchased Aerostreet products. The sampling technique applied is Non-Probability Sampling. SmartPLS software version 3 was used to analyze data using the Partial Least Square (PLS-SEM) method. This study shows that Content Marketing and Live Shopping have a positive and significant effect on buying interest. It is hoped that this study can help companies in creating effective marketing strategies on social media, especially on the TikTok Shop platform, to increase customer buying interest